2009
DOI: 10.1007/s11033-009-9913-8
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a functional flavanone-3ß-hydroxylase gene from Medicago truncatula

Abstract: As a key enzyme in the biosynthesis of flavonols, anthocyanidins and proanthocyanidins, flavanone-3ß-hydroxylase (F3H) plays very important roles in plant stress response. A putative flavanone-3ß-hydroxylase gene from Medicago truncatula (MtF3H), a model legume species, was identified from a bio-data analysis platform. It was speculated to be induced by salt stress based on the outcomes of the analysis platform. The complementary DNA (cDNA) consists of 1499 bp with an open reading frame (ORF) of 1098 bp, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Similar observations were made in Arabidopsis where several regulatory genes indicated upregulation in roots exposed to salt treatment whereas shoots showed upregulation under osmotic stress 51 . Also, M. truncatula exposed to salt stress for 12 and 24 hours presented higher expression of the flavanone 3 hydroxylase gene in roots compared to leaves and stems 52 . Seven genes SOS1, SOS2, SOS3, HKT1, OTS1, SGF29 , and SAL1 were consistently upregulated in the roots of the genotypes that performed well for biomass yield and physiological parameters ( Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Similar observations were made in Arabidopsis where several regulatory genes indicated upregulation in roots exposed to salt treatment whereas shoots showed upregulation under osmotic stress 51 . Also, M. truncatula exposed to salt stress for 12 and 24 hours presented higher expression of the flavanone 3 hydroxylase gene in roots compared to leaves and stems 52 . Seven genes SOS1, SOS2, SOS3, HKT1, OTS1, SGF29 , and SAL1 were consistently upregulated in the roots of the genotypes that performed well for biomass yield and physiological parameters ( Fig.…”
Section: Discussionmentioning
confidence: 92%
“…OSCP is often considered to be a part of the F 0 sector of the ATPase and associated with the energy generation (Horak et al ., ). Favanone 3β‐hydroxylase (F3H), as a key enzyme in the biosynthesis of flavonols, anthocyanidins and proanthocyanidins, plays very important roles in plant stress response (Shen et al ., ). Both of the genes could be induced by salt stress in our experiment, and the two target genes and miRNAs had certain correlation at the level of post‐transcription, indicating that miRNAs can regulate energy synthesis and reduction oxidation.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, the bryophyte enzyme also generated kaempferol from dihydrokaempferol, demonstrating that FNSIs can also act as FLS enzymes by recognizing not only flavanones but also flavanonols (Han et al, 2014). In relation to the catalytic activity of the F3H enzyme used in the present work, it has been shown that it lacks FNS or FLS activity and cannot generate apigenin or kaempferol from naringenin or dihydrokaempferol, respectively (Wellmann et al, 2004;Shen et al, 2010); however, as far as we know, there are no references to its suspected F2H activity. Therefore, the close evolutionary relationship between F3H and FNSI, along with the F2H activity described for an FNSI, leads us to hypothesize that our F3H (encoded in pGR and pDF recombinant vectors) can have an F2H side activity allowing the formation of 2hydroxyliquiritigenin and 2-hydroxynaringenin (spectrum signals coming from putative 2-hydroxydihydrokaempferol were also detected, but no commercial standard was available).…”
Section: Discussionmentioning
confidence: 54%